2014
DOI: 10.1634/theoncologist.2014-0169
|View full text |Cite
|
Sign up to set email alerts
|

Lichenoid Mucosal Reaction to Rituximab

Abstract: A case of rituximab‐induced oral lichenoid drug reaction in a patient with follicular non‐Hodgkin lymphoma is presented. In light of the wide use of rituximab for the treatment of lymphoma and the increasing use for autoimmune diseases, awareness and recognition of this unusual side effect of treatment with rituximab is critical to allow for prompt management to reduce morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 7 publications
(10 reference statements)
0
18
1
1
Order By: Relevance
“…In 2012, a case study conducted by Bakkour and Coulson reported a widespread cutaneous lichenoid eruption related to the administration of obinutuzumab, a new anti-CD20 monoclonal antibody, in a patient with relapsed follicular lymphoma previously treated with rituximab [5]. Two years later, Kuten-Shorrer et al reported the first case of OLDR in a patient treated with rituximab for a stage IIIA follicular lymphoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a case study conducted by Bakkour and Coulson reported a widespread cutaneous lichenoid eruption related to the administration of obinutuzumab, a new anti-CD20 monoclonal antibody, in a patient with relapsed follicular lymphoma previously treated with rituximab [5]. Two years later, Kuten-Shorrer et al reported the first case of OLDR in a patient treated with rituximab for a stage IIIA follicular lymphoma [17].…”
Section: Discussionmentioning
confidence: 99%
“…Lichenoid drug eruptions are relatively common and occur secondary to numerous medications including β-adrenergic blockers, antimalarials, penicillamine, quinine, gold-containing substances, antihypertensive medications, proton pump inhibitors, intravenous immunoglobulins (IVIGs), monoclonal antibodies against tumor necrosis factor-alpha (TNF-α; eg, etanercept, adalimumab, infliximab), and anti-CD20 (rituximab). 28 -31 Numerous case reports of lichenoid eruptions secondary to ICIs have been described. Lichenoid eruptions occur more frequently with anti-PD-1/anti-PD-L1 agents rather than with CTLA-4 inhibitors.…”
Section: Lichenoid Reactionsmentioning
confidence: 99%
“…LR can disappear, either immediately after the agent's action is completed, or can persist. [55] In addition, histologic examination reveals eosinophilic infiltration, prominent parakeratosis with acanthosis, and a vascular inflammation around the deep plexuses. These histologic features are absent in OLP.…”
Section: Lichenoid Reactionsmentioning
confidence: 99%
“…[57] It is responsible for lichenoid lesions in the oral mucosa, skin, or nails. [55,56,58] Suggestions have been expressed concerning the pathogenesis of LRs and LRs relationship with chemotherapy. Imatinib is responsible for the altered expression of epidermal markers.…”
Section: Lichenoid Reactionsmentioning
confidence: 99%